A Literature Review of the Use of Weeds and Agricultural and Food Industry By-Products to Feed Farmed Crickets (Insecta; Orthoptera; Gryllidae) - Kuo, Camille; Fisher, Brian L. (Frontiers in Sustainable Food Systems, 2022)
Global socioeconomic systems exacerbate disparities that leave a disturbing proportion of the human population malnourished, making conventional food sources such as animal livestock unsustainable at global scales. Edible insects have the potential to solve both malnourishment and the unsustainability of conventional livestock agriculture. The sustainability and accessibility of farmed, edible insects, however, depends on their feed source. Future expansion of farming rests on developing locally available and affordable insect feeds. This article presents a literature review of studies which evaluate the performance of edible crickets (Orthoptera) in response to alternative feed sources such as weeds and the byproducts of agricultural and food industries. For each insect species evaluated, we analyze measurements of feed and insect performance, feed composition, effects of diet on cricket growth and survivorship, as well as other sources of performance differences. The aim of this review is to assess the current state of alternative feed research for farmed crickets and to provide guidelines for future studies on alternative feeds.